The Effect of Self-Development Program for Improving Independence in Defective Students in SLB N 1 Lima Kaum Batusangkar - Aulia Rahmah; Eric Rouns; Aedro Luck (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2022)
Students with mental retardation are seen as less likely to have independence, especially those who occupy the Extraordinary Elementary School (SDLB) and are most dominantly difficult to be independent. All of his activities and needs still depend on his parents. One way to increase the independence of mentally retarded students is through self-development programs. This research method is qualitative research by collecting observation data and interviews with three mentally retarded students. The results of this study are teachers train and teach self-development programs to students so that students are able to be independent. The conclusion is that the self-development program, which is activated by the teacher to students and aims to achieve independence, has been successfully realized.